2014
DOI: 10.1021/nl500214e
|View full text |Cite
|
Sign up to set email alerts
|

Modular Plasmonic Nanocarriers for Efficient and Targeted Delivery of Cancer-Therapeutic siRNA

Abstract: We have combined a versatile and powerful route to deliver nucleic acids with peptide-based cell-specific targeting. siRNA targeting the polo-like kinase gene is in clinical trials for cancer treatment, and here we deliver this RNA selectively to cancer cells displaying the neuropilin-1 epitope using gold nanoshells. Release of the siRNA from the nanoparticles results from irradiation with a pulsed near-infrared laser, which also provides efficient endosomal escape within the cell. As a result, our approach re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 42 publications
1
78
0
Order By: Relevance
“…NIR light can be tightly focused threedimensionally (down to ≈1 fL) [27] and reach deep through tissues (up to 10 cm). [28,29] Small interfering RNAs (siRNAs) with thiol-modification are covalently attached to hollow gold nanoshells (HGNs) via quasicovalent AuS bonds, [30][31][32] followed by the functionalization of a cell-penetrating transactivating transcriptional activator (TAT) peptide. [33] Upon endosomal uptake, NIR light irradiation releases the RNAs from the…”
Section: Doi: 101002/adma201603318mentioning
confidence: 99%
“…NIR light can be tightly focused threedimensionally (down to ≈1 fL) [27] and reach deep through tissues (up to 10 cm). [28,29] Small interfering RNAs (siRNAs) with thiol-modification are covalently attached to hollow gold nanoshells (HGNs) via quasicovalent AuS bonds, [30][31][32] followed by the functionalization of a cell-penetrating transactivating transcriptional activator (TAT) peptide. [33] Upon endosomal uptake, NIR light irradiation releases the RNAs from the…”
Section: Doi: 101002/adma201603318mentioning
confidence: 99%
“…Cells were washed by adding 1.2 mL cold PBS, centrifuging at 55 Â g for 3 min and resuspending in 45 mL cold PBS. Tubes with~50 mL of cell suspension were irradiated with 2.4 W/cm 2 pulsed NIR laser for 15 s by the output of a femtosecond Ti:sapphire regenerative amplifier (Spectraphysics Spitfire) with the same setup as previously described [35,36]. The laser beam diameter was~4 mm with the spectral range of 800 ± 6 nm, and the pulse duration was 130 fs with the repetition rate at 1 kHz.…”
Section: Particle Transfection and Femtosecond Laser Irradiationmentioning
confidence: 99%
“…Multiple copies of functional siRNA molecules were conjugated to the surface of the~50 nm diameter HGN through a quasi-covalent AueS bond, whereas uptake of the construct by hESC was mediated by the TAT-peptide coating on the particle surface. Upon pulsed NIR laser irradiation, the HGNs strongly absorb pulsed NIR laser light, which is rapidly (nanosecond) converted to heat, ablating the AueS bond holding the siRNA on HGN surface and producing transient vapor bubbles that ruptures the endosome without damaging the siRNA [36] or the hESC (Fig. 1a).…”
Section: Construction and Characterization Of Tat-peptide Coated Hgnsmentioning
confidence: 99%
See 1 more Smart Citation
“…After cell uptake, we supposed that the large number of positive charges within Arg-G4 nanoparticles could be protonated in acidic endosomes, causing the endosomes to swell and finally burst to release the cargo. 29,30 However, the detailed transfection mechanism needs to be investigated in the further study. It has been reported that the arginine-terminated PAMAM of lower generation from Arg-G1 to Arg-G3 showed weak siRNA delivering activity.…”
mentioning
confidence: 99%